Pengaruh Model Pembelajaran Kooperatif Paired Storytelling Berbantuan Media Video Dalam Meningkatkan Keaktifan Dani Motivasi Belajari Siswa Kelas VIII SMP Negeri 4 Masbagik - Rahmi Inawati; Muhammad Rapii; Agus Riswanto (Alpatih Harapan Semesta, 2026)
This study aims to test the influence mode of cooperative learning Paired Storytelling assisted by video media on the activeness and motivation of learning of class VIII SMPN 4 Masbagiki in 2025. This study adapts a quantitative methodology using a Nonequivalent Control Group Design. The sample consists of two classes, namely the experimental class and the control class. The instrument is a questionnaire on activeness and motivation of learning that has been tested for validity and reliability. Data analysis was carried out in the form of non-normality tests, homogeneity tests, paired sample tests, and independent sample tests with a significance level of 0.05. The results of the analysis indicate that the Paired Storytelling model assisted by video media has a significant effect on increasing students' activeness and motivation of learning. The average value of activity increased from 25.95 to 43.67 (a 68.2% increase), while learning motivation increased from 64.15 to 83.85 (a 30.7% increase). The test results indicated a significance value of 0.000<0.05, which means there was a significant difference between before and after the treatment. Thus, the Paired Storytelling model assisted by video media is effective in creating an active, interactive, and enjoyable learning atmosphere.